Lipotropic activities of aqueous extract of Vernonia guineensis Benth. in Wistar rats fed high fat diet - Leila Sandra Nnanga; Bruno Dupon Akamba Ambamba; Fils Armand Ella; Damaris Enyegue Mandob; Judith Laure Ngondi (BMC, 2022)
Abstract Background Lipotropic molecules are effective therapeutic targets to counteract non-alcoholic fatty liver disease (NAFLD). Lipotropic compounds are capable of removing fat from the liver and/or manage the reduction of the synthesis or deposition of lipids in the liver. The objective of this study was to evaluate the lipotropic effects of the aqueous extract of leaves of Vernonia guineensis (AEVG) on rats fed high fat diet. Methods Twenty male rats with an average mass of 235 g were allow acclimatize for seven days, following which they were divided into four groups of five animals each. The test group was treated with high fat diet (HFD) and AEVG at 400 mg/kgBW, while positive control group received HFD and Fenofibrate at 100 mg/kgBW. The normal control group received a normal diet; and the negative control group received HFD. After 14 days of treatment, animals were sacrificed, blood and organs (liver, heart and kidneys), as well as the faeces were collected for the preparation of plasma and homogenates respectively. Some markers of lipid profil (total cholesterol, triglycerides, HDL-c, LDL-c,) and markers of toxicity (AST, ALT, γ-GT, creatinine) were evaluated. Results The results obtained showed that a HFD at the hepatic level led to the accumulation of lipids (triglycerides (TG) and total cholesterol (TC)) and had adverse effects on hepatic function by promoting cytolysis. At the plasma level, HFD induced hyperlipidemia. Administration of AEVG at 400 mg/kgBW improved the blood lipid profile and reduced the storage of TG and cholesterol in the liver. AEVG also promoted fecal cholesterol excretion and reduced atherogenic indices which include Total Cholesterol/High-Density Lipoprotein cholesterol (TC/HDL-c) and Low-Density Lipoprotein cholesterol/High-Density Lipoprotein cholesterol (LDL-c/HDL-c). The extract exhibited hepato-protective activity (anticholestasis) and improved glomerular filtration. Conclusion These findings suggest that AEVG possesses lipotropic effects confirming its probable use in the management of non-alcoholic fatty liver disease and its cardiometabolic complications. This virtue could be exploited for local pharmaceutical development.